Nineteenth Century Navies Role in Developing an understanding of the Pacific Coast of Central America - León Sáenz, Jorge (Universidad de Costa Rica, 2018)
Navies, apart from their traditional use by nations as instruments for the projection of power, for the protection of maritime interests and for exercising peacekeeping and war activities, have also had an important role in developing scientific and technical knowledge.  The survey work undertaken by various navies since the 18th century, has in particular been of great benefit in improving and making navigation safer on high seas and coasts, through the provision of maritime charts and sailing directions, to all mariners.  The technical efforts and geopolitical interests behind those efforts in the 19th century and how they affected the maritime trade and foreign affairs of the Central American countries located on the Pacific Coast are the subject of this study.